A Case Report of Vascular Ectasias of GI Tract Presenting as Occult Gastro-Intestinal Bleed Diagnosed on Capsule Endoscopy (Journal of Medicine, 2020)
Abstract Not AvailableJ MEDICINE JUL 2020; 21 (2) : 117-118